From Cubic Palladium to Concave Core-Shell Platinum Palladium Nanoparticles: Evolution of the Structure and Their Electrochemical Properties. Issue 3 (1st January 2018) - Tymen, Simon; Scheinost, Andreas C.; Lozano-Rodriguez, M. Janeth; Friebe, Christian; Schubert, Ulrich S.
Abstract : The PtPd nanoparticles are synthesized following different methods and intensively investigated for their catalytic properties oxygen reduction reaction (ORR), with a potential application in fuel cells. The galvanic replacement is an attractive method to prepare bimetallic particles with high catalytic activity and a high control of the morphology and chemical composition, varying with the experimental conditions during the synthesis. The influence of the time with the transformation from pure Pd nanocubes to concave core-shell PtPd nanoparticles synthesized by galvanic replacement is examined: after different times of preparation, the morphology of the particles was monitored by transmission electron microscopy (TEM) coupled with energy Dispersive X-ray spectroscopy (EDS). Via X-Ray diffraction spectroscopy (XRD), the crystallographic structure and the variation of size, lattice parameters, d-spacing, and composition were determined. The extended X-ray fine structure (EXAFS) measurements show the formation of a PtPd alloy at the surface of the particles for all samples. Finally, the electrochemical determination of the catalytic activity and stability tests revealed two different particle types as candidates to replace pure Pt as catalyst in the proton exchange membrane fuel cells (PEMFC) due to their enhanced stability, higher catalytic activity, and lower Pt content.